Corruption at the grassroots : the shades and shadows - Narayanasamy, N.; Boraian, M. P.; Jeyaraju, M. A.; National Workshop on "Corruption at the Grassroots", (1998 : Madras, India) (New Delhi : Concept Pub. Co., 2000)
Papers presented at the National Workshop on "Corruption at the Grassroots" held at Chennai on Dec. 3, 1998.
Includes bibliographical references and index.
Keywords: Political corruption -- India; Misconduct in office -- India; Bribery -- India